Comparative Study of Response between Concurrent Chemoradiation and Sequential Chemoradiation in the treatment of Locally Advanced Base of Tongue Carcinoma in a limited resource setting (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Introduction: Base tongue carcinoma is commonly diagnosed an advanced stage in low-resource settings. Concurrent chemoradiotherapy (CCRT) and sequential chemoradiotherapy (SCRT) after induction chemotherapy are both used, but their comparative effectiveness remains unclear in such contexts.Aim of the study: The study aimed to compare the treatment response and acute toxicities between concurrent chemoradiotherapy and sequential chemoradiotherapy in patients with locally advanced base of tongue carcinoma in a limited-resource setting.Methods: The study was conducted using a purposive sampling technique at the National Institute of Cancer Research and Hospital (NICRH), Dhaka, over 12 months (June 2016–May 2017). A total of 60 patients with histopathologically confirmed squamous cell carcinoma of the base of tongue at stage III or IVA were enrolled and randomized into two equal groups. Arm A received concurrent chemoradiotherapy (CCRT) with external beam radiotherapy (66 Gy in 33 fractions over 6½ weeks) using the 3D Conformal Radiotherapy (3DCRT) technique, along with weekly cisplatin (40 mg/m²). Arm B received three cycles of induction chemotherapy (cisplatin 75 mg/m² on Day 1 and 5-FU 750 mg/m²/day for 3 days, every 3 weeks), followed by the same CCRT as Arm A. Data were analyzed using SPSS v22.0, employing descriptive statistics and Chi-square/Fisher’s exact tests, with p